Return to Sport after Disc Herniation: A Comprehensive Review of Conservative and Surgical Treatment Approaches - Al-Saadi, Ahmed; Veihelmann, Andreas (Sportverletzung · Sportschaden, 2025)
Back pain (BP) is a globally prevalent musculoskeletal disorder, affecting up to 85% of individuals at some point in their lives. It significantly affects quality of life and productivity, with a particularly high prevalence in athletes due to the high physical demands of their activity. This review examines the comparative effectiveness of conservative and surgical treatments for patients with disc herniation (DH), focusing on their return-to-sport (RTS) outcomes.A systematic review was conducted of studies evaluating RTS following conservative or surgical treatment of patients with DH. Databases including PubMed, MEDLINE, and EMBASE were searched for studies reporting RTS rates, recovery times, and long-term performance outcomes, with a focus on adult athletes.A total of 16 studies were included in this systematic review, consisting of retrospective and prospective cohort studies, randomised controlled trials, and case-control designs. These studies were specifically selected for their relevance to RTS outcomes following conservative or surgical treatment of intervertebral disc herniation in athletes. Collectively, the studies included approximately 2,500 athletes across various sports, such as football (NFL), soccer (Serie A), basketball (NBA), baseball (MLB), hockey (NHL), rugby, tennis, and rowing. Both conservative treatments (e.g., physical therapy) and surgical interventions (e.g., microdiscectomy) demonstrated high RTS rates, ranging from 78.9% to 97%. Athletes treated conservatively typically returned to play faster (4.7 months on average), whereas surgical treatment was associated with a slightly higher long-term RTS success (up to 97%) and recovery times ranging from 5.2 to 5.8 months. Notably, no significant long-term performance impairments were observed.Both treatment modalities were effective, with surgical approaches offering particular benefits for patients with neurological deficits or severe disc degeneration. Conservative treatment was associated with faster recovery, supporting its use as a first-line approach for patients with mild symptoms or athletes requiring rapid RTS.While both conservative and surgical treatments yield high RTS rates, the decision must be individualised based on the patient’s symptom severity, neurological status, and sport-specific demands. Future studies should focus on optimising treatment protocols and developing standardised RTS criteria tailored to elite athletes for improved long-term functional outcomes.
Keywords: Return to Sport (RTS); Disc Herniation (DH); Conservative Treatment; Microdiscectomy; Athlete Rehabilitation